A Review on Integration of Traditional and Modern Medicine - N. Udayakumar1, (Asian Journal of Pharmaceutics (AJP), 2025)
Modern healthcare systems face several challenges in delivering comprehensive patient care, necessitating innovative approaches that combine traditional and contemporary medical practices. A synergistic integration of traditional medicine systems, such as Ayurveda, Traditional Chinese Medicine, and indigenous healing practices with modern medical interventions offers promising solutions for enhanced healthcare delivery. Traditional medicine’s focuses on personalized care, preventive approaches, and holistic healing complements modern medicine’s technological advancement and evidence-based methodologies. Integration studies demonstrate improved patient outcomes in chronic disease management, particularly in diabetes, pain management, and mental health conditions. The incorporation of traditional practices enhances cultural competence in healthcare delivery while addressing the diverse needs of global populations. Clinical evidence supports the efficacy of combined therapeutic approaches, such as acupuncture with conventional pain management and traditional herbal remedies with modern pharmacotherapy. However, standardization of traditional practices, quality control measures, and regulatory frameworks remain critical challenges. Building effective partnerships between traditional healers and modern healthcare professionals requires systematic approaches to overcome communication barriers and establish common ground. Present research validates traditional practices through scientific methods, strengthening the foundation for integrated healthcare delivery. The development of standardized protocols, combined with rigorous safety and efficacy assessments, paves the way for a more inclusive and effective global healthcare system that respects both traditional wisdom and modern medical advances.